Mental Health as Common Lifestyle - Alamsyah, Dani; Merdeka, Pijar Hatinurani (EDUPEDIA Publisher, 2023)
This academic paper delves into the intricate realm of mental health, investigating its impact on the emotional, cognitive, and psychological well-being of individuals. Recognizing the diverse nature of human responses to life's challenges, this paper underscores the importance of effectively managing emotions and stresses. Drawing insights from scholarly sources and the World Health Organization (WHO), the paper highlights the multifaceted nature of mental health and its role in realizing an individual's potential. It explores the significance of a balanced mental state in fostering normalcy, productivity, and positive interpersonal relationships. Additionally, this paper explores the genesis of mental disorders during adolescence and the subsequent repercussions, emphasizing the importance of early intervention and support. The paper also catalogues prevalent mental health disorders such as depression, insomnia, schizophrenia, bipolar disorder, and schizoaffective disorder, offering insights into their distinct characteristics. It then navigates through treatment approaches encompassing drug consumption, psychotherapy, and family therapy, which form essential pillars in the restoration of mental equilibrium. This paper concludes by reaffirming the essentiality of mental health in human existence and advocating for collective efforts to foster a supportive environment conducive to mental well-being.